Gender Discrimination in America: An In-depth Analysis - Charles Grey (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Gender discrimination remains a pervasive issue in the United States, despite significant progress in the fight for gender equality over the past century. This scholarly article aims to provide an in-depth analysis of gender discrimination in America, focusing on its historical context, contemporary manifestations, and the ongoing efforts to combat it. By examining the roots of gender discrimination, its impact on various aspects of society, and the policy measures implemented to address it, this article seeks to shed light on the complex nature of this social problem.